La Relación de Santa Cruz Pachacuti Yamqui: un reflejo de la ética andina - Beauclair, Nicolas (2016)
The Relación of Joan de Santa Cruz Pachacuti Yamqui Salcamaygua is a unique colonial text and one of the few to tell Andean pre-Hispanic history by the hand of a member of an indigenous community. However, while giving rise to a fairly large number of studies and reviews, it has not yet reached a full consensus whether its contents are authentically Andean or the result of a process of acculturation. In this article, we re-examine this monumental work from a less studied viewpoint, that is, the possible posture adopted by Pachacuti Yamqui to write is Relación and that he let appear through the use of discursive traditions and the subject of enunciation of the work.